The role of exosomes in metastasis and progression of melanoma - Gowda, Raghavendra; Robertson, Bailey M.; Iyer, Soumya; Barry, John; Dinavahi, Saketh S.; Robertson, Gavin P. (Cancer treatment reviews, 2020)
•Tumor-derived or tumor-associated exosomes (usually 30–100 nm in diameter) released by the tumor cells are important facilitators of intercellular communication involved in the pathogenesis, development, progression, and metastasis of cancer.•Exosomes are become attractive new biomarkers for the diagnosis and prognosis of cancer.•Clinical trials to determine the feasibility of exosomes for use as a biomarker, biological target, or drug delivery vehicle to treat a wide variety of human disease conditions are being explored.•This review discusses the multifaceted role of melanoma-derived exosomes in promoting the process of metastasis by modulating the invasive and angiogenic capacity of malignant cells. The mechanisms of melanoma metastasis have been the subject of extensive research for decades. Improved diagnostic and therapeutic strategies are of increasing importance for the treatment of melanoma due to its high burden of mortality in the advanced stages of the disease. Intercellular communication is a critical event for the progression of cancer. Collective evidence suggests that exosomes, small extracellular membrane vesicles released by the cells, are important facilitators of intercellular communication between the cells and the surrounding environment. Although the emerging field of exosomes is rapidly gaining traction in the scientific community, there is limited knowledge regarding the role of exosomes in melanoma. This review discusses the multifaceted role of melanoma-derived exosomes in promoting the process of metastasis by modulating the invasive and angiogenic capacity of malignant cells. The future implications of exosome research and the therapeutic potential of exosomes are also discussed.